Delamination buckling of GFRP-strips in strengthened RC beams. (15th November 2022) - Capozucca, R.; Magagnini, E.; Bettucci, E.
Abstract: Fiber Reinforced Polymer (FRP) strips are convenient materials in the strengthening of damaged RC beams of bridges due to corrosion or impact loading and in the rehabilitation of RC beams damaged by seismic actions. The behaviour of Externally Bonded (EB) FRP strips has been extensively studied when the strengthening is subjected to tensile stresses, even if, in many cases, due to cyclic actions, FRP strips glued to the concrete surface may be subjected to compression. Compressive stresses on the FRP strip may cause a buckling mechanism with detachment. In this work, an investigation of reinforced concrete (RC) beam models undamaged and damaged and strengthened with GFRP strips on compressive and tensile sides is shown. Beam models were subjected to four-point bending tests and the delamination buckling mechanism of the GFRP strip has been described. Further, analytical models to study the delamination buckling of strengthening with FRP strips are developed. Finally, experimental and theoretical data are discussed.